PENJADWALAN FLOW SHOP DENGAN PENERAPAN CROSS ENTROPY-GENETIC ALGORITHM (CEGA) UNTUK MEMINIMASI MAKESPAN - Bashori, Hasan; Pratikto, Pratikto; Sugiono, Sugiono (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2015)
Abstract In this study done on leather shoe company that uses flow shop scheduling strategies. Where the purpose of this study is to minimize makespan is the total time needed to complete the entire job. This is done because of the large demand for leather shoes that exceeds the production capacity and production scheduling by the company based on intuition. In solving the production scheduling problem that occurs in the company, Cross Entropy algorithm used method-Genetic Algorithm (CEGA) to minimize the makespan. From the results of calculations with CEGA method sequences obtained by scheduling makespan value of 5822 seconds with an efficiency of 6.79% when compared with the method of the company with sebasar makespan value of 6246 seconds.